Paper No 19.1: Industrial Aspects of Material Development for Organic Field Effect Transistors: High‐Mobility Organic Semiconductors for Large‐Area Deposition. (September 2013) - Budry, J.‐L.; Bujard, P.; Chebotareva, N.; Düggeli, M.; Flores, J.‐C.; Hayoz, P.; Mathauer, K.; Martin, E.; Prétôt, R.; van der Schaaf, P.; Vaidyanathan, S.; Brill, J.; et al.
Abstract: Since its first introduction to the scientific community in 2005, N, N‐dialkyl‐3, 6‐diheteroaryl‐derivatives of 3, 6‐diaryl‐diketopyrrolopyrrole (commonly nicknamed DPP) have been intensively studied as new class of functional materials. This paper will demonstrate that optimization of processing conditions has a dramatic effect on transistor performance leading to not only a 30‐fold improvement in mobility, from 0.1 to 3 cm 2 .V‐ 1 .s‐ 1, but also high Ion/Ioff ratio, very good homogeneity and reproducibility. Those results, generated while using spinless processes in non‐chlorinated aromatic solvents, are compatible with large area deposition techniques. An emphasis on the slit‐coating technique and the different important parameters to control the morphology of the semiconductor will be made.